Relationships between Excitation Voltage and Performance of AFWR Synchronous Generator - Abdul Multi; Iwa Garniwa (Universitas Ahmad Dahlan, 2013)
The axial flux wound rotor generator has field winding that should be connected to a dc voltage source. Varying the excitation voltage, its electric performance might be controlled to meet the need of a load voltage attached to its terminal. The generator designed is small-scale capacity which has 1 kW, 380 V and 750 rpm. The generator has a single double-sided slotted wound stator sandwiched between twin rotor. The effect of excitation voltage changes on its performance can be seen from the result of calculations using the given equations.The calculation results reveal electric quantities suited with respect to performance of the machine. If the voltage is higher then the losses will be lower. However, the higher the voltage, the higher the efficiency and the torque.It has been found out that for the excitation voltage11 V, the efficiency and the torque are 85.12 % and 13.04 Nm respectively.